Fair Lady: effective coverage of politics in a women’s magazine - Boshoff, Chanél and Fourie, Lynnette and Swanepoel, Thalyta (2010)
"The article discusses the coverage of politics in South African women’s magazine Fair Lady in selected years from democratisation in 1994 to ten years later in 2004. In a democracy, the media has the explicit duty to inform society. Within this context three questions are asked: (1) Which political themes are covered? (2) In what genres do the political items feature? (3) In what ways does the magazine focus the reader’s attention on political items? These aspects were selected to provide a clear view of the extent and manner in which Fair Lady presents politics in its content. This study was done by means of a qualitative content analysis. By focusing on these issues and by drawing on the functions of the media; the agenda setting theory; the schema theory and the on-line evaluation theory, it is argued that the magazine deems politics as important and incorporates it on its agenda to provide readers with necessary political information which they might not otherwise attain. Fair Lady overcomes the fact that politics does not traditionally feature in women’s magazines by taking care in attracting and keeping readers’ attention to political items. The publication (especially in 2004) can be held up as an example to other women’s magazines trying to fulfil their function as a medium to educate and inform readers whilst at the same time not alienating the entertainment-seekers."[Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-19184